Politik Kejahatan Perang oleh Rusia dalam Perang Chechnya II, 1999-2009 - Rosemaya, Reivina; Utomo, Tri Cahyo (Journal of International Relations, 2018)
Chechnya is a small region of Russian Federation at Caucasus which Muslims are itsmajority. Chechnya demands on independence but the Russian Federation won’t passed it.The difference between their interests caused unsolved conflicts that led them intoChechnya War II. It is believed that Russian army committed war crimes during this war.This undergraduate thesis is questioned: why did Russian committed war crimes during theChechnya War II 1999 – 2009? The aims of this undergraduate thesis is to seek Russia’sinterests on commiting war crimes at Chechnya War II using theory of offensive realism.Explanative case study is used in this undergraduate thesis. Based on theory that used inthis undergraduate thesis, to reach its interest Russia is responsible for their continouslyaggressive attacks that caused many victims from civilians. The result is war crimes thatcommitted by Russia are led by its interest to hold its status quo toward Chechnya.